High Performance Speed Control of Single-Phase Induction Motors Using Switching Forward and Backward EKF Strategy - Mohammad Jannati; Tole Sutikno; Nik Rumzi Nik Idris; Mohd Junaidi Abdul Aziz (Institute of Advanced Engineering and Science, 2016)
The aim of this research is to provide a high performance vector control of single-phase Induction Motor (IM) drives. It is shown that in the rotating reference frame, the single-phase IM equations can be separated into forward and backward equations with the balanced structure. Based on this, a method for vector control of the single-phase IM, using two modified Rotor Field-Oriented Control (RFOC) algorithms is presented. In order to accommodate forward and backward rotor fluxes in the presented controller, an Extended Kalman Filter (EKF) with two different forward and backward currents that are switched interchangeably (switching forward and backward EKF), is proposed. Simulation results illustrate the effectiveness of the proposed algorithm.